PENERAPAN LKPD BERBASIS KEMAMPUAN ARGUMENTASI-SWH UNTUK MENINGKATKAN KEMAMPUAN ARGUMENTASI TERTULIS DAN LITERASI SAINS SISWA - Kusdiningsih, Erni Zaskia (FKIP Universitas Lampung, 2016)
The Implementation of Student Worksheet based Argument – SWH Ability for Writing Argumentation Ability and Improve Scientific Literacy of Students. The purpose of this research was to find written argumentability and saw an increase in students’ science literacy through student worksheet based argumentation – SWH abilities. The method used is a quasi-experimental. The design of this research was pretest and posttest non equivalent between the experiment class and control class. The result shawed that using student worksheet written argumentation ability skill get sufficient characterized that was 71%. The results showed that were significant difference between in the experimental class with N-gain that was 0.72 and the control class with N-gain that was 0.16. Keywords: students’ worksheet, argumentation, scientific literacy DOI: http://dx.doi.org/10.23960/jpp.v6.i2.201601